Letters from Tayyib Gökbilgin’s Private Collection: László Rásonyi - Kutse Altın (Tarih Dergisi)
As one of the most prominent figures in Ottoman historiography, Tayyib Gökbilgin (1907-1981) started his studies as a former teacher who’d graduated from Dârülmuallimîn alongside the famous Turcologist László Rásonyi in 1936 as the first student of the Department of Hungarology at the Ankara University Faculty of Language, History, and Geography. László Rásonyi presented a paper at the Second Language Congress held by the Turkish Language Association in 1934 and was invited to the Faculty of Language, History, and Geography as a lecturer to establish the Department of Hungarian Studies at Atatürk’s request. The main focus of this article is to present some examples of the letters László Rásonyi sent as the founder of the Department of Hungarian Studies to Gökbilgin, his first student and later colleague. Tayyib Gökbilgin’s private archive has an excellent collection for a close study of his transnational intellectual and scientific network. These letters not only provide insight into his personal and professional contacts, but also explain the motivation behind his careful preservation of the letters.The collection is also invaluable as it provides powerful testimony to how transnational intellectual and scholarly networks among academicians survived almost uninterruptedly thanks to their extraordinary efforts, dedication, and struggles despite the difficulties caused by politics.